Peningkatan Hasil Belajar Menggunakan Model Pembelajaran Kooperatif Tipe Think Pair Share di Sekolah Dasar - Fetriani, Lezia; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
The dismal academic performance of today's pupils is a driving force behind this study. With the Think-Pair-Share (TPS) Cooperative Learning Model as its basis, this research seeks to enhance the effectiveness of integrated thematic learning. Using both qualitative and quantitative methods, this study was a classroom action research (PTK). Two cycles of planning, carrying out, observing, and reflecting. This research included 13 fourth-graders and their instructors. There was an improvement from the first cycle's 84.71% (excellent) to the second cycle's 94.44% (Very excellent) in most facets of the lesson plans. Teachers' engagement in cycle I was generally favourable at 83.92% (Good), and it improved to a very satisfying 92.85% (Excellent) in cycle II. Students in Cycle I scored an average of 78.58% on the activity component, which improved to an impressive 92.85% in Cycle II. The average learning outcome of students in cycle I, which was 67.40 (Enough), improved to 85.14 (Good) in cycle II. These results suggest that SD Negeri 87 Bengkulu Selatan's fourth graders may benefit from adopting the TPS cooperative learning model. The benefit for students is increasing learning outcomes, while for teachers it is being able to create an active and innovative learning environment, creating students who are independent and able to work together which leads to the achievement of learning objectives.